Does Patient Counselling Correspond to Medication Adherence in Chronic Diseases? - A Scoping Review - Basnet, Rojina; Bhandari, Rajan; Gautam, Sabyata; Lama, Nishant; K.C., Shreejana; Bhandari, Tulsi Ram (Journal of Karnali Academy of Health Sciences, 2021)
Background: Quality care is essential to minimize the complication or consequences of chronic diseases. The main objective of this scoping review was to identify the role of patient counseling on medication adherence in chronic diseases. Methods: Scoping review framework, as described by Arksey and O’Malley was used to map out the literature. Databases were searched for published studies from 1 to 30 August 2020 which described medication adherence, factors contributing and role of patient counseling in medication adherence. Results: Total 21 primary studies, including 29% were randomized controlled trials designs and 76% of studies were conducted in the hospital setting. The medication non-adherence in the chronic disease was between 12-33% in reviewed studies. Conclusion: Most of the studies identified patient counseling as a major contributing factor for drug adherence in terms of chronic diseases. Similarly, pharmacist’s communication with patient is also described as important factor for medication non-adherence in reviewed articles. Thus, efforts must be broadened to improve counseling services within the health system to overcome chronic diseases through addressing drug non-adherence. Practical Implication: The findings of this review would be relevant for all health professionals, medical persons, and pharmacists to sensitize them about the importance of counseling in terms of overcoming chronic diseases.